Dietary Manipulations Using Oil Palm (Elaeis Guineensis) Fronds to Increase the Unsaturated Fatty Acid Content Of Mutton under Tropical Conditions - Goh, Yong Meng (2002)
Forty-three seven-month old Barbados Black Belly x Malin crossbred rams were used for the first trial which lasted 14 weeks, inclusive of two weeks of adjustment period. They were allotted into three treatment groups fed varying levels of oil palm (Elaeis guineensis) frond pellets and commercial sheep pellets. Treatment diets were 80% commercial pellet + 20% (% w/w) oil palm frond pellet (CON group, n=15), 50% commercial pellet + 50% oil palm frond pellet (% w/w) (HAF group, n=14) and 80% oil palm frond pellet + 20% (% w/w) commercial pellet (OPF group, n=14). The total lipids were extracted using the Folch method and methylated using 14% methanolic Boron triflouride with a known added amount of heneicosanoic acid (21:0) as an internal standard. The fatty acid methyl esters were separated by capillary column gas liquid chromatography and the fatty acids quantitated as absolute amounts or as percentage of total fatty acids. The plasma and tissues of the CON animals had significantly (P<0.05) increased levels of unsaturated fatty acids (UFA) at the end of the trial compared to their initial values and both HAF and OPF groups. The increase in the UFA content was mainly due to the increased monounsaturated fatty acid (MUFA) content. The plasma and tissues of the HAF animals had the highest amount of saturated fatty acids (SFA) proportionately and in absolute amounts among the three treatment groups. The fatty acid unsaturation status of the plasma and tissues from the OPF animals was midway between those of the CON and HAF groups. All groups had low concentrations of EFA with unfavourable n-6:n-3 ratios. However, the CON animals had more (P<0.05) n-6 PUFA in their tissues, whereas the n-3 PUFA were more abundant (P<0.05) in the OPF animals. It was also noticed that the forequarter muscles were lower in n-3 PUFA compared to the hindquarter muscles. Generally, the plasma lipids of the sheep were not markedly affected by their respective treatment diets. The weight gain was the highest in the CON group at 113 g/d and the lowest in the OPF group at 35 g/d. The carcass (Table 20) and meat characteristics (Table 21) obtained from 34 slaughtered animals were significantly different (P<0.05) between treatment groups with the best traits observed in the CON animals. Nine surviving animals (three for each treatment group) from the first trial were used for the second trial. Oesophageal intubations were carried out at zero, two, four, six and eight hours post feeding on each animal to determine the changes in the rumen conditions due to the treatment diets. The rumen pH was significantly different (P<0.05) between treatment groups. It was always in the decreasing order of OPF>HAF>CON at all time points. The rumen volatile fatty acids, ammonia nitrogen content, bacterial and protozoal counts were significantly different (P<0.05) between groups as well. The marked differences in the rumen conditions had resulted in the highest (P<0.05) amount of UFA present in the rumen of CON animals even after eight hours post-feeding. The UFA in the rumen contents of the CON animals (63.7 ± 6.1 mg/lOOmL) was two fold higher than those of HAF animals (31.9 ± 4.9 mg/100mL), and quadruple that of the OPF animals (12.1 ± 1.5 mg/1OOmL) at this point. Subsequently, this had led to the higher levels of UFA in the CON tissues and plasma as shown in the first trial. In the third trial, seventy-five individually housed male Sprague-Dawley rats aged between six to seven months were used. Fifteen rats were selected randomly and sacrificed to establish the initial baseline values for the serum lipids at the onset of the trial. The remaining 60 rats were allotted randomly into five groups of 12 animals each. Three groups were fed with meat pellets derived from the mutton in the first trial. One group was fed with meat pellets prepared from commercially available mutton whole carcass for comparison purposes, and another group fed with standard rat chow as control. Blood and arterial tissue samples were obtained from the euthanised rats. Sampling was done on four animals from each group sacrificed serially at two, four and six weeks after the onset of the trial. Results showed that the CON mutton increased the rat serum HDL-Cholesterol significantly (P<0.05) over those fed with the commercially available mutton. The serum HDLCholesterol levels in the CON mutton fed rats was 1.09 ± 0.31 mmol/L, while those fed commercially available mutton was 0.79 ± 0.10 mmol/L. The results on other serum lipids and arterial lesions were inconclusive. In summary, the dietary manipulations demonstrated the feasibility of increasing the mutton UFA content to a level that would promote healthy changes in the consumers' blood lipid profiles, using sheep reared under tropical conditions fed diets formulated from oil palm frond pellets and commercial concentrates.